Analisis Metode Inkuiri Berbasis CTL dalam Keterampilan Membedakan Antara Fakta dan Opini dari Berbagai Laporan Lisan di SMA Negeri 5 Medan - Syifa Aramitha Lubis; Tantri Adelia; Annisa Luthfiyah3; Putri Husnul Khotimah Harahap; Meutiah Khairani Harahap; Robianna Harahap; Budiman Budiman (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research was conducted to have several destinations. First aims to design learning in the subject of the ignition system using the CTL learning strategy. Second aims to implement a CTL learning strategy in Indonesian language subjects. Third aims to improve the activation and learning outcomes of students using CTL's learning strategy. This study is a class study, in the learning process, implementing CTL learning strategies. The target of this study is a class XI IPA-3 high school student 5 Medan. The activation aspects of students observed by an observer include paying attention to the teacher's explanation, asking the ununderstand material, responding/answering questions, listening to the explanation of copying/recording the teacher, material, and solving/answering the problem. The activation of students was observed through direct observation into the classroom during the learning process and teaching to take place.